Sepsis in burn patients: Is there difference? - Kanlerd, Amonpon (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2024)
Sepsis is still the major cause of death, even in burns. Severe burn patients who survived the initial phase may combat infection subsequently, and sepsis becomes the primary cause of death afterward. Sepsis and septic shock in severe burns usually result from pneumonia, urinary tract infection, catheter-related bloodstream infection, or burn wound infection. Diagnosis of sepsis in severe burns might be difficult because of the mimicking of clinical signs and laboratory results. Clinical prediction scores such as SOFA and biomarkers such as procalcitonin are developed for screening and diagnosing sepsis in burns. Treating sepsis in burns consists of rapid identification of infectious sources and control, hemodynamic support with adequate fluid resuscitation and vasopressor, and appropriate antibiotics.